The Effectiveness of Sialang Honey in Burn Healing Through the Expression of Vascular Endothelial Growth Factor (VEGF) in Rattus norvegicus - Firdath Rubenzani; Syamsul Rizal; Mirnasari Amirsyah; Budiman Budiman; Khairan Khairan (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Full-thickness burns require rapid revascularization to prevent tissue necrosis and support the healing process. Sialang honey, a wild multifloral honey from Indonesia, has traditionally been used for wound care, but its specific mechanism in modulating angiogenesis remains poorly understood. This study aimed to evaluate the effectiveness of Sialang honey on the expression of Vascular Endothelial Growth Factor (VEGF) in a mouse model with full-thickness burns. A true experimental study with a post-test only control group design was conducted using 27 male Wistar rats (Rattus norvegicus). Full-thickness burns were induced and treated daily for 14 days. Rats were randomly divided into three groups: Negative Control (0.9% NaCl), Treatment (Topical Sialang Honey), and Positive Control (1% Silver Sulfadiazine). Skin tissue was collected on days 5, 7, and 14. VEGF expression was detected using immunohistochemical (IHC) staining and measured via H-Score. Data were analyzed using One-Way ANOVA and Post-Hoc LSD Test (p<0.05). Treatment with Sialang Honey significantly increased VEGF expression compared to the negative control group. Peak expression occurred on day 7 (mean difference vs. control: p=0.000), indicating strong angiogenesis during the proliferation phase. Notably, VEGF levels in the honey group decreased significantly on day 14 (p<0.05), mimicking the physiological transition to the remodeling phase. The honey group showed a superior angiogenic response compared to Silver Sulfadiazine on day 7. Sialang honey effectively accelerated burn wound healing by modulating VEGF expression promoting an initial surge in angiogenesis followed by a physiological decline. These findings support the potential of Sialang honey as an effective topical agent for burn management. Keywords: Sialang Honey, Vascular Endothelial Growth Factor (VEGF), Angiogenesis.